Rancang Bangun Sistem Informasi Praktek Kerja Industri Berbasis Web (Studi Kasus: Smk Al-Azhar Menganti Gresik) - Ningsih, Puji Wahyu; Lusiani, Titik; Nurcahyawati, Vivine (Jurnal JSIKA, 2012)
SMK Al-Azhar Menganti Gresik is a technical education organization which in its educational process works along with worldwide industry through Internship  program (prakerin). Prakerin needs an adequate plan by the school and industry to gain sucessfull, effective and efficient implementation. Furthermore, SMK Al-Azhar in order to fullfil its needs still facing problems to plan the prakerin; the administration section for prakerin are struggling to develop the prakerin data to make the prakerin schedule and can’t decide the right working-placement for student based on student criteria and a qualification that industry make. In addition, there aren’t any marking result reports which is used by the school to monitor the desired expecation level from prakerin impelemtation program. To solve the problems described, there should be an information system which can develop the prakerin data to gain the right placement for student based on its criteria and the qualification from industry. This information system can also evaluate the marking result for the school to monitor the desired expectation level from prakerin implementation program. Lastly, through this internship information system which is built by web-based, developing the prakerin data can work well and the information that the system made can also be used by the school to monitor the desired expectation level from prakerin implementaion program. Keywords: praktek kerja industri, monitoring, prakerin.